Autologous Stem Cell Transplantation in Multiple Myeloma Patients Over 60 Years Old - Bahar Uncu Ulu; Tuğçe Nur Yiğenoğlu; Semih Başcı; Mehmet Bakırtaş; Derya Şahin; Tahir Darçın; Jale Yıldız; Alparslan Merdin; Nuran Ahu Baysal; Dicle İskender; Mehmet Sinan Dal; Merih Kızıl Çakar; Fevzi Altuntaş (Medical Laboratory Technology Journal, 2021)
The incidence of Multiple myeloma (MM) increases with age; two-thirds of the patients are older than 65 years. Induction treatment, including new agents such as thalidomide, bortezomib, and lenalidomide followed by a conditioning regimen and upfront autologous stem cell transplantation (ASCT), has been accepted the standard treatment approach for newly diagnosed fit MM patients. We aimed to search the real-life data, the efficacy and safety of upfront ASCT following induction in patients with MM over 60 years old retrospectively. The data of MM patients who were ≥60 years old during autologous stem cell transplantation and treated at our center between 2010 and 2018 retrospectively analyzed. The study results were 63 patients included at the age of ≥ 60 years who underwent upfront ASCT. Median PFS was 15.5±2.6 months, and the median overall survival (OS) was 28.15±5 months. According to age groups, median PFS was 12±2.3 months in the 60-64 age group, 18.4±6 months in the 65-69 age group, and 26±15 months in the ≥70 age group. Median OS was 26.5±6.1 months in the 60-64 age group, 39.66±8.9 months in the 65-69 age group, and 18 months in the ≥70 age group. A significant relationship between the quantity of infused CD34+ stem cells and PFS and OS (p:0.05 and p